Group Counseling Deactivation Mode to Improve Psychological Well-Being of Students - Barida, Muya; Widyastuti, Dian Ari; Krisphianti, Yuanita Dwi; Ahmad, Aslina; Rofiah, Nurul Hidayati; Andriyani, Andriyani; Mashar, Riana; Saraswaty, Emiko (Jurnal Kajian Bimbingan dan Konseling, 2025)
Life moves dynamically, profoundly impacting adolescents and often causing deep anxiety due to numerous pressures. The gap between expectations and reality frequently exacerbates this anxiety. Ideally, adolescents should be equipped to manage their inner lives to prevent excessive anxiety, and individuals can better manage anxiety if they possess strong psychological well-being. This study aims to improve psychological well-being through a group counseling deactivation mode. The research applied an experimental research method with a one group pretest-posttest design. Participants consisting of junior high school students in Yogyakarta, selected through purposive sampling for their low psychological well-being levels. Data on psychological well-being were collected using a validated and reliable psychological well-being scale. Data analysis was conducted using the Wilcoxon formula. Results: The Wilcoxon test results show that the significance value is 0.043 (< 0.05). This means that there is a significant difference in the psychological well-being of students between before and after implementing the Deactivation Group Counseling Mode model. The results indicate that the group counseling deactivation mode effectively improves psychological well-being. Limitations of this study include a small, region-specific sample, lack of a control group, brief intervention duration, and reliance on self-report measures, which may limit generalizability and introduce potential bias. Future research should address these limitations by utilizing larger, more diverse samples, implementing a randomized controlled trial design, assessing long-term effects, and incorporating qualitative methods to gain deeper insights into the intervention's impact.